Contrastando o português paulista e o português gaúcho.: Interpretação da formalidade dos pronomes sujeito de segunda pessoa do singular - Pereira, Ronan (Revista da Associação Portuguesa de Linguística, 2022)
Brazilian Portuguese, regarding its second person singular pronouns, is seen by some authors as a dyadic system: the pronoun "você" is the informal pronoun, while "o senhor" is used in situations that require more formality. Although the canonical informal pronoun “tu” still occurs, it is considered that “tu” and “você” are not in complementary distribution, their choice being mostly the result of diatopic variation, with a region where the use of “você” is dominant (e.g. the state of São Paulo), another one where the use of “tu” is dominant (e.g. the state of Rio Grande do Sul), and their more balanced coexistence in a third zone (the largest one in territory). Also, when “tu” occurs, it is generally followed by a verb with third person inflection morphology, although differences can be observed regarding this phenomenon as well. Pereira (2021), based on the specific scenario found in Rio Grande do Sul (predominance of “tu”, with low rates of canonical inflection), conducted a formality judgement test with native speakers of that dialect and found out they actually attributed different levels of formality regarding the type of pronoun used in the sentences, evincing what seems to be a triadic system, at least regarding the speakers’ representation, composed by, from the most informal to the most formal, “tu” (with third person inflection), “você” – paired with “tu” with the canonical inflection –, and “o senhor”. Thus, this study aimed to replicate Pereira’s (2021) study with participants who lived and had been raised in the state of São Paulo, since “você” is predominant there. The results showed a similar gradient of formality, although not identical averages, with different sociolinguistic factors (age, schooling, and gender) affecting the results. Moreover, “tu” with the canonical inflection was paired to “o senhor” at the formal extreme of the scale, which might be due to the fact it is a rarer form and speakers only have contact with it in situations regarded as formal (e.g., in Portuguese grammars or textbooks at school). Thus, the data and comparisons brought out in this study demonstrate the relevance of uniting different methodologies as to reach more robust conclusions regarding the different phenomena in variation in Brazilian Portuguese.